Successful Management Of Gingival Enlargement By Gingivectomy: A Case Report - Nike Omaya Nusaiba; Aprilia Yuanita Anwaristi (CV. AFDIFAL MAJU BERKAH, 2026)
Gingival enlargement is a pathological condition characterized by an increase in the size and volume of gingival tissue, which may impair oral function, esthetics, and oral hygiene maintenance. The management of this condition depends on the underlying etiology and severity of gingival tissue enlargement. This case report aimed to describe the successful management of gingival enlargement using gingivectomy in the mandibular anterior region. A 28-year-old male patient presented with a chief complaint of gingival enlargement involving teeth 41 and 42 that had persisted for approximately one year without pain. Clinical examination revealed localized gingival enlargement accompanied by periodontal pocket depths of up to 5 mm. Initial periodontal therapy consisting of scaling and root planing was performed, followed by conventional gingivectomy and gingivoplasty to restore physiological gingival contours.